Bioenergetics profile of CD4+ T cells in relapsing remitting multiple sclerosis subjects - De Riccardis, Lidia; Rizzello, Antonia; Ferramosca, Alessandra; Urso, Emanuela; De Robertis, Francesca; Danieli, Antonio; Giudetti, Anna Maria; Trianni, Giorgio; Zara, Vincenzo; Maffia, Michele (Journal of biotechnology, 2015)
Multiple sclerosis (MS) is a chronic inflammatory autoimmune demyelinating disease of the central nervous system. There are four clinical forms of MS, the most common of which is characterized by a relapsing remitting course (RRMS). The etiology of MS is unknown, but many studies suggested that genetic, environmental and infectious agents may contribute to the development of this disease. In experimental autoimmune encephalomyelitis (EAE), the animal model for MS, it has been shown that CD4+ T cells play a key role in MS pathogenesis. In fact, these cells are able to cross the blood–brain barrier and cause axonal damage with neuronal death. T cell activation critically depends on mitochondrial ATP synthesis and reactive oxygen species (ROS) production. Interestingly, lots of studies linked the oxidative damage arising from mitochondrial changes to neurodegenerative disorders, such as MS. Based on these evidences, this work focused on the metabolic reprogramming of CD4+ T cells in MS subjects, being this cell population directly implicated in pathogenesis of disease, paying attention to mitochondrial function and response to oxidative stress. Such aspects, once clarified, may open new opportunities for a therapeutic metabolic modulation of MS disorder.